Urinary Metabolomics Reveals Alterations of Aromatic Amino Acid Metabolism of Alzheimer’s Disease in the Transgenic CRND8 Mice - Tang, Zhi; Liu, Liangfeng; Li, Yongle; Dong, Jiyang; Li, Min; Huang, Jiandong; Lin, Shuhai; Cai, Zongwei (Current Alzheimer Research, 2016)
Alzheimer’s disease (AD) is a progressive neurodegenerative disorder, with amyloid plaques accumulation as the key feature involved in its pathology. To date, however, the biochemical changes in AD have not been clearly characterized. Here, we present that urinary metabolomics based on high resolution mass spectrometry was employed for delineation of metabolic alterations in transgenic CRND8 mice. In this noninvasive approach, urinary metabolome reveals the biochemical changes in early onset of this AD mouse model. In virtue of comprehensive metabolite profiling and multivariate statistical analysis, a total of 73 differential metabolites of urine sample sets was identified in 12-week and 18-week transgenic mice compared to wild-type littermates, covering perturbations of aromatic amino acid metabolism, the Krebs cycle and one-carbon metabolism. Of particular interest is that divergent tryptophan metabolism, such as upregulation of serotonin pathway while downregulation of kynurenine pathway, was observed. Meanwhile, the accumulation of both N-acetylvanilalanine and 3-methoxytyrosine indicated aromatic L-amino acid decarboxylase deficiency. And the microbial metabolites derived from aromatic amino acid metabolism and drug-like phase II metabolic response via the glycine conjugation reactions were also highlighted, indicating that genetic modification in mouse brain not only alters genotype but also perturbs the gut microbiome. Together, our study demonstrated that the integrative approach employing mass spectrometry-based metabolomics and a transgenic mouse model for AD may provide new evidence for distinct metabolic signatures. The perturbations of metabolic pathways may have far-reaching implications for early diagnosis and intervention in AD.
Keywords: metabolomics